2015
DOI: 10.5296/jmr.v7i2.6928
|View full text |Cite
|
Sign up to set email alerts
|

Abuse of the Malaysian Elderly: An Analysis on the Adequacy and Suitability of the Domestic Violence Act 1994 (Act 521) to Protect the Elderly Victim

Abstract: Abuse of the elderly is not a new issue at the international level. It is seen as a serious social problem that is a growing concern. A number of countries have enacted specific legal mechanisms to address and prevent the problem. In Malaysia, the abuse of the elderly is recognized as a form of domestic violence. The legislation dealing with matters pertaining to domestic violence is Domestic Violence Act 1994 (Act 521) which is to be read together with Penal Code. The Domestic Violence Act (DVA) becomes the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The problem is that it can only cover a few types of elder abuse. The remaining parts, such as abandonment, inancial, and neglect, are not included (Bidin and Yusoff, 2015). An analysis based on the provision in the Domestic Violence Act 1994 showed that the existing legislation is inadequate to provide full protection to the elderly victims and signi icant amendments are required (Bidin and Yusoff, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The problem is that it can only cover a few types of elder abuse. The remaining parts, such as abandonment, inancial, and neglect, are not included (Bidin and Yusoff, 2015). An analysis based on the provision in the Domestic Violence Act 1994 showed that the existing legislation is inadequate to provide full protection to the elderly victims and signi icant amendments are required (Bidin and Yusoff, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the Domestic Violence of Act only covers a few parts of elder abuse. These include physical abuse and sexual abuse (Bidin and Yusoff, 2015). One of the suggestions includes the Legislature amending the Domestic Violence Act, adding a clause pertaining to elder abuse.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This study also believes there is room for improvement in providing proper treatment for the older person in Malaysia. For instance, a study conducted by Bidin and Mohd Yusoff (2015) shows the incidence of abuse among the older person. Their study found that the provisions in the Domestic Violence Act (DVA) reveal the existing legislation is not sufficient to give full protection to the older person from neglect misconduct and abuse.…”
Section: …] I'm Experiencing This Very Odd Feeling I Think It Might mentioning
confidence: 99%